1982
DOI: 10.1007/bf01870770
|View full text |Cite
|
Sign up to set email alerts
|

The role of sodium-channel density in the natriferic response of the toad urinary bladder to an antidiuretic hormone

Abstract: Urinary bladders of Bufo marinus were depolarized, by raising the serosal K concentration, to facilitate voltage-clamping of the apical membrane. Passive Na transport across the apical membrane was then studied with near-instantaneous current-voltage curves obtained before and after eliciting a natriferic response with oxytocin. Fitting with the constant-field equation showed that the natriferic effect is accounted for by an increase in the apical Na permeability. It is accompanied by a small increase in cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 33 publications
10
70
1
Order By: Relevance
“…Our results in the CCT confirm the presence of saturation of the singlechannel conductance, although half saturation was at a somewhat higher concentration than that of the A6 cell channel (75 mM vs. 17-47 mM). This concentration is also higher than that required to half-saturate short-circuit current in amphibian epithelia (13,18,19) or net Na fluxes across the rabbit CCT (20). This discrepancy could result in part from a decrease in the driving force for Na or from a reduction in the number ofopen channels when external Na is increased in the transepithelial measurements.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results in the CCT confirm the presence of saturation of the singlechannel conductance, although half saturation was at a somewhat higher concentration than that of the A6 cell channel (75 mM vs. 17-47 mM). This concentration is also higher than that required to half-saturate short-circuit current in amphibian epithelia (13,18,19) or net Na fluxes across the rabbit CCT (20). This discrepancy could result in part from a decrease in the driving force for Na or from a reduction in the number ofopen channels when external Na is increased in the transepithelial measurements.…”
Section: Discussionmentioning
confidence: 97%
“…The dependence of single-channel conductance on apical (pipet) Na is of interest because Na transport across many tight epithelia is a saturable function of apical Na with half saturation in the range of 10-30 mM (13,(18)(19)(20). Using fluctuation analysis, Van Driessche and Lindemann (21) found that single-channel currents in the frog skin did not saturate, but rather the number of conducting channels decreased with increasing apical Na.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, channels may be acquired from a pool of quiescent channels already present in the membrane (Li, Palmer, Edelman & Lindemann, 1982). In epithelial cells cytoskeletal proteins mediate important membrane functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vasopressin increases sodium transport in frog skin and toad urinary bladder via cyclic AMP as suggested first by Orloff & Handler (1967). Recent work has shown that vasopressin recruits electrically silent channels without affecting the mean life-time or unit conductance of individual channels (Li, Palmer, Edelman & Lindemann, 1981). In this way the recruitment of silent channels accounts for the macroscopic increase in sodium SCC.…”
Section: Introductionmentioning
confidence: 86%